SiOx encapsulated FeSi2–Si eutectic nanoparticles as durable anode of lithium-ion batteries. (August 2021) - Qiu, Z.; Wu, A.; Jin, X.; Zhou, S.; Yu, W.; Huang, H.
Abstract: Low-cost and high-efficiency production of silicon-based material is the key to improve the energy density of lithium-ion batteries. Herein, we propose a novel structure of FeSi2 –Si eutectic nanoparticles protected by the SiOx shell. FeSi2, as a buffer phase can improve the electrochemical stability of the electrode. A SiOx shell is formed on the surface of the nanoparticles through the passivation process. SiOx encapsulated FeSi2 –Si eutectic nanoparticles exhibit excellent capacity of 674.9 mAh/g after 500 charge/discharge cycles. The capacity retention rate is above 90% after the stabilization process. This work provides a new nanomaterial design for high performance silicon-based anode materials of lithium-ion batteries. Graphical abstract: Image 1 Highlights: The SiOx -encapsulated FeSi2 –Si eutectic nanoparticles are fabricated by the plasma evaporation method. The nanoparticles deliver the discharge capacity of 674.9 mAh/g after 500 cycles. The high capacities and superior cyclic stability are root from the excellent conductivity FeSi2 and stable SiOx .